Pengaruh Penerapan Standar ISO 27001 : 2013 terhadap Keamanan Data Pribadi Pengguna Teknologi Finansial - Imas Masyrifah; Magnaz Lestira Oktaroza (Bandung Conference Series: Accountancy, 2022)
Abstract. The current development of financial technology is required to be able to provide convenience for the public in using financial services. Activities such as payments, transfers, buying and selling securities and cash loans must be done digitally and with an easy process. All the conveniences that occur due to technological developments can threaten the security of various things, one of which is the security of information and personal data of financial technology users. Therefore, it is deemed necessary to have protection for personal information or data that can guarantee the confidentiality and security of such data. ISO (International Organization for Standardization) is a control that specifically prioritizes information security factors which are often used as a reference for implementing information system security. With the implementation of the ISO 27001 standard, it will be able to protect aspects of information security, namely confidentiality, integrity and availability. Based on this phenomenon, the formulation of the problem in this study is: How does the application of ISO 27001: 2013 standards affect the security of personal data of financial technology users?. The method used in this research is descriptive and verification method using a quantitative approach. Sources of data for this study were taken frommembers of the Bandung City FKP community. In this study, data collection was carried out by distributing questionnaires, the sampling technique in this study used a convenience sampling technique, namely by making the total respondents a sample of 38 members. Furthermore, the data were analyzed using simple linear regression analysis and hypothesis testing. The results of this study indicate that the application of the ISO 27001: 2013 standard has a positive and significant effect on the security of personal data of financial technology users. Abstrak. Perkembangan fintech saat ini dituntut untuk mampu memudahkan masyarakat dalam menggunakan layanan keuangan. Segala kemudahan-kemudahan yang terjadi akibat perkembangan teknologi dapat mengancam keamanan berbagai hal, salah satunya yaitu keamanan informasi dan data pribadi pengguna teknologi financial. Maka dari itu, dipandang perlu akan adanya perlindungan bagi informasi ataupun data pribadi yang dapat menjamin kerahasiaan dan keamanan bagi data tersebut. ISO 27001 adalah suatu pengendalian yang sangat mengutamakan keamanan informasi yang kerap digunakan sebagai acuan untuk menerapkan keamanan sistem informasi yang dapat melindungi aspek-aspek keamanan informasi yaitu kerahasiaan, keutuhan dan ketersediaan. Melihat dari fenomena tersebut maka didapatkan rumusan masalah sebagai berikut : Bagaimana pengaruh penerapan standar ISO 27001 : 2013 terhadap keamanan data pribadi pengguna teknologi finansial ? dalam peneelitian ini, metode yang digunakan yaitu metodeverifikatif dengan menggunakan pendekatan kuantitatif. Sumber data untuk penelitian ini diambil dari pelaku UMKM yang tergabung dalam komunitas FKP Kota Bandung. Pengumpulan data dilakukan dengan cara menyebarkan kuesioner, dengan teknik sampling yaitu teknik convenience sampling yang dengan menjadikan total responden menjadi sample yaitu sebanyak 38 anggota. Selanjutnya data dianalisis menggunakan analisis regresi linear sederhana dan pengujian hipotesis. Hasil penelitian ini menunjukan bahwa penerapan standar ISO 27001 : 2013 berpengaruh positif dan signifikan terhadap keamanan data pribadi penggun teknologi finansial.